Autonomic markers of emotional processing: skin sympathetic nerve activity in humans during exposure to emotionally charged images - Brown, Rachael; James, Cheree; Henderson, Luke; Macefield, Vaughan G. (Frontiers in Physiology, 2012)
The sympathetic innervation of the skin primarily subserves thermoregulation, but the system has also been commandeered as a means of expressing emotion. While it is known that the level of skin sympathetic nerve activity (SSNA) is affected by anxiety, the majority of emotional studies have utilized the galvanic skin response as a means of inferring increases in SSNA. The purpose of the present study was to characterize the changes in SSNA when showing subjects neutral or emotionally-charged images from the International Affective Picture System. Skin sympathetic nerve activity was recorded via tungsten microelectrodes inserted into cutaneous fascicles of the common peroneal nerve in ten subjects. Neutral images, positively-charged images (erotica) or negatively-charged images (mutilation) were presented in blocks of fifteen images of a specific type, each block lasting two minutes. Images of erotica or mutilation were presented in a quasi-random fashion, each block following a block of neutral images. Both images of erotica or images of mutilation caused significant increases in SSNA, but the increases in SSNA were greater for mutilation. The increases in SSNA were often coupled with sweat release and cutaneous vasoconstriction, however, these markers were not always consistent with the SSNA increases. We conclude that SSNA, comprising cutaneous vasoconstrictor and sudomotor activity, increases with both positively-charged and negatively-charged emotional images. Measurement of SSNA provides a more comprehensive assessment of sympathetic outflow to the skin than does the use of sweat release alone as a marker of emotional processing.